PHRASEOLOHICAL UNITS IN GERMAN JORNALISM AS OBJECT OF INTERDISCIPLINARY APPROACH - S. V. Alikova; O. S. Shibkova (Гуманитарные и юридические исследования)
The article is devoted to the stylistic features of phraseology in politic-economic journalism, correlating with their expressive potential. The theoretical analysis and taxonomic method allow to characterize the journalistic style in modern times and identify the phraseological classification whereas the main classifying features are the meaning and structure. The authors emphasize the appropriateness of the multidisciplinary approach in further studies of phraseology.